THE USE OF STORYTELLING ASSISTED WITH PICTURE SERIES TO IMPROVE SPEAKING SKILL - Arnoldus Ardi; Dewa Ayu Ari Wiryadi Joni; I Gusti Agung Putri Wirastuti (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
This study used classroom action research design which was conducted in two cycles in which each cycle consisted of two sessions. The subject was class IX F of SMP (SLUB) Saraswati 1 Denpasar which consisted of 38 students. In this present study, the research instruments used were tests (pre-test, post-test 1, and post-test 2) and questionnaire. The result of the pre-test showed that the students' ability in speaking was still low. They still had problems with vocabulary, grammar, pronunciation, comprehension, and fluency. To solve that problem, the researcher used storytelling technique assisted with picture series that was carried out in two cycles. Based on the data of pre-test, post-test 1, and post-test 2 which were respectively 60.52, 70.13, and 80.52, it showed that there were improvements in speaking when they retold the narrative story. In addition, the questionnaire data showed that there were positive responses towards the implementation of storytelling technique in improving the subjects’ speaking skill. In conclusion, this study research proved that speaking skill of the ninth-grade students of SMP (SLUB) Saraswati 1 Denpasar in academic year 2022/2023 can be improved through storytelling technique assisted with picture series.